2021
DOI: 10.3390/antibiotics10101146
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the Profile of Hospital-Acquired Infections in Adult Intensive Care Units

Abstract: Hospital-acquired infections (HAIs) are a global public health concern. As the COVID-19 pandemic continues, its contribution to mortality and antimicrobial resistance (AMR) grows, particularly in intensive care units (ICUs). A two-year retrospective study from April 2019–April 2021 was conducted in an adult ICU at the Hospital for Infectious and Tropical Diseases, Belgrade, Serbia to assess causative agents of HAIs and AMR rates, with the COVID-19 pandemic ensuing halfway through the study. Resistance rates &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 61 publications
0
26
1
Order By: Relevance
“…Acinetobacter spp was among the least isolated organisms in this study together with Staphylococcus saprophyticus, Streptococci viridians, Proteus mirabilis and Leuconostoc mesenteroid spp with only one isolate of each discovered. This is contrary to other reports from Bangladesh [25] where Acinetobacter spp was found to be the dominant cause of hospital acquired infection and the most frequently isolated organisms in COVID-19 patients compared to the non-COVID-19 patients. Another study in South Africa [22] also reported Acinetobacter spp as the most frequently isolated organisms among ICU COVID-19 patients followed by Klebsiella spp.…”
Section: Prevalence Of Co-infectionscontrasting
confidence: 99%
“…Acinetobacter spp was among the least isolated organisms in this study together with Staphylococcus saprophyticus, Streptococci viridians, Proteus mirabilis and Leuconostoc mesenteroid spp with only one isolate of each discovered. This is contrary to other reports from Bangladesh [25] where Acinetobacter spp was found to be the dominant cause of hospital acquired infection and the most frequently isolated organisms in COVID-19 patients compared to the non-COVID-19 patients. Another study in South Africa [22] also reported Acinetobacter spp as the most frequently isolated organisms among ICU COVID-19 patients followed by Klebsiella spp.…”
Section: Prevalence Of Co-infectionscontrasting
confidence: 99%
“…The survival outcomes among critically ill preterm surgical neonates are very dim and infections are among the leading cause of their mortality [ 2 ]. While some articles reported lowered HAI ratios during the ongoing COVID-19 related emergency state [ 3 ], in general, infection numbers have grown worryingly, despite the overall increased mask wearing and hand hygiene practices, according to the CDC ( , accessed on 15 June 2022) and International Reports [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This ranged from an increase in CRE rates from 6% in Turkey [18], 35% in the US [26] to 54% in Italy [33] and also definitive changes in Brazilian ICUs, where according to trend analysis, the monthly incidence density of CRE per 1000 PDs showed a gradual increase [12 & ]. In Serbia, an association between the diagnosis of COVID-19 and increased resistance to all carbapenems (imipenem and meropenem P < 0.001; ertapenem P ¼ 0.03) was observed [34]. From a species point of view, a significant increase in K. pneumoniae carbapenemase (KPC) À producing K. pneumoniae was observed in ICU patients in a large Italian hospital [28], as were colonization rates [28,35].…”
Section: Carbapenem-resistant Enterobacterales/ Carbapenemase-produci...mentioning
confidence: 94%